2020
DOI: 10.1371/journal.pone.0239672
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of a recombinant fortilin from Fenneropenaeus merguiensis

Abstract: Human Fortilin, an antiapoptotic protein, has also been implicated in several diseases; however, several potential uses of fortilin have also been proposed. Bearing the implications of fortilin in mind, fortilin analog, which has no complication with diseases, is required. Since a recombinant full-length fortilin from Fenneropenaeus merguiensis (rFm-Fortilin (FL)) reported only 44% (3e-27) homologous to human fortilin, therefore the biological activities of the Fm-Fortilin (FL) and its fragments (F2, F12, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…In addition, the full-length fortilin did not trigger histamine release from PBMCs. Based on the amino acid sequence alignment, Pmer-fortilin only shares approximately 44% similarity with its human counterpart [14]. Therefore, Pmer-fortilin may not contain the domain responsible for stimulation of histamine release and is unlikely to activate an immune reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the full-length fortilin did not trigger histamine release from PBMCs. Based on the amino acid sequence alignment, Pmer-fortilin only shares approximately 44% similarity with its human counterpart [14]. Therefore, Pmer-fortilin may not contain the domain responsible for stimulation of histamine release and is unlikely to activate an immune reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant fortilin from Penaeus merguiensis (Pmer-fortilin) was shown to have an anti-apoptotic function in HEMA-treated human dental pulp cells [12,13]. A previous study showed that Pmer-fortilin shares approximately 44% similarity with its human counterpart [14]. Fortilin was reported to have anti-apoptotic activity across different species, and its respective mechanisms were demonstrated through several pathways [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Fm-Fortilin gene derived from F. merguiensis was cloned and expressed in Escherichia coli ( E. coli ) strain BL21 (DE3) following the method previously described. 13 Briefly, E. coli strain BL21 (DE3) harboring pET29a-Fm-Fortilin was inoculated into 10 mL of Luria–Bertani (LB) medium containing 30 μg/mL kanamycin. After incubation for 16–18 h, the culture was grown in 500 mL of LB medium containing kanamycin until the cell density reached optical density (OD) at 600 nm = 0.6.…”
Section: Methodsmentioning
confidence: 99%
“…TCTP proteins present proliferative properties and antiapoptotic activity, and TCTP from Fenneropenaeus merguiensis (banana prawn) was explored as supplements in dental restorative materials (Wanachottrakul et al, 2011). This TCTP was shown to promote osteoblast cells proliferation, differentiation and function, highlighting its potential use as a supplementary medical material in dentistry (Sangsuwan et al, 2015;Kedjarune-Leggat et al, 2020). TCTP ability to protect cells in a range of stress conditions was recently described in cardiomyocytes (Cai et al, 2019).…”
Section: Translationally Controlled Tumor Protein: Target Candidates In Histamine-related Pathologies and As Pro-proliferative Biomateriamentioning
confidence: 99%
“…(2019)) • Development of analgesic drugs (Cardoso et al (2017), Dongol et al (2019))• Development of antifungal(Ayroza et al (2012)), antiarrhythmic(Bode et al (2001)) and antimalarial(Choi et al (2004)) drugs • Biological inputs to be used as imaging agents for tumor detection(Moore et al (2013);Kintzing and Cochran. (2016)) TCTP (22 kDa)• Biotool to be used in studies regarding parasites biology or biological input to be used in the development of vaccines against parasites(Bhisutthibhan et al (1998);Taylor et al (2015))• Development of drug delivery systems(Bae et al (2018)) • Biotechnological input to be used as dental restorative material(Wanachottrakul et al (2011), Sangsuwan et al (2015,Kedjarune-Leggat et al (2020))…”
mentioning
confidence: 99%